2012
DOI: 10.1117/1.jbo.17.7.075005
|View full text |Cite
|
Sign up to set email alerts
|

Anterior corneal asphericity calculated by the tangential radius of curvature

Abstract: Abstract. We propose a method of calculating the corneal asphericity (Q) and analyze the characteristics of the anterior corneal shape using the tangential radius. Fifty-eight right eyes of 58 subjects were evaluated using the Orbscan II corneal topographer. The Q-values of the flat principal semi-meridians calculated by the sagittal radius were compared to those by the tangential radius. Variation in the Q-value with semi-meridian in the nasal and temporal cornea calculated by the tangential radius was analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…This study found that the corneal Q values of the anterior surface at 3.0, 5.0 and 7.0mm aperture diameters were -0.29 ± 0.18, -0.28 ± 0.18 and -0.29 ± 0.18, respectively, while some previous studies reported the corneal Q value to be -0.33 (Carney (Australian) [13], Ying (Chinese) [14]), -0.22 (Cheung (Chinese) [15], Scholz (German) [16]), -0.24 (Dubbelman (Dutch) [17]), -0.08 (Horner (Indian) [18]), -0.20 (Fuller (American Caucasian) [6]), -0.26 (Fuller (Africa-American) [6]), -0.346 (Davis (American) [19]), and -0.30 (Zhang (Chinese) [9]). In these studies, the maximum corneal Q value was -0.08, while the minimum value was -0.346.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…This study found that the corneal Q values of the anterior surface at 3.0, 5.0 and 7.0mm aperture diameters were -0.29 ± 0.18, -0.28 ± 0.18 and -0.29 ± 0.18, respectively, while some previous studies reported the corneal Q value to be -0.33 (Carney (Australian) [13], Ying (Chinese) [14]), -0.22 (Cheung (Chinese) [15], Scholz (German) [16]), -0.24 (Dubbelman (Dutch) [17]), -0.08 (Horner (Indian) [18]), -0.20 (Fuller (American Caucasian) [6]), -0.26 (Fuller (Africa-American) [6]), -0.346 (Davis (American) [19]), and -0.30 (Zhang (Chinese) [9]). In these studies, the maximum corneal Q value was -0.08, while the minimum value was -0.346.…”
Section: Discussionmentioning
confidence: 69%
“…Only Ying [14] used the same instrument as we used, and all other studies used different methods. For example: Scholz [16] utilized Tracey iTrace visual function analyzer with integrated EyeSys vista corneal topography, which uses a placido-based videokeratoscope that calculates the Q value by combining the anterior and posterior surfaces as a whole.…”
Section: Discussionmentioning
confidence: 99%
“…This might be explained by the fact that Choi and colleagues calculated the axial (sagittal) radius of the sclera while in the studies of Hall et al [11,12] and in this study the tangential scleral radius was assessed. As the tangential radius requires no assumption concerning the location of the optic axis, the tangential radius gives a truer picture of off-axis irregularities than the sagittal radius [26][27][28]; hence the tangential radius seems to be more useful then the sagittal measurement in the detection of topographic abnormalities and surface shape changes, as in accurate GP base curve selection [28][29][30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…The tangential radius of curvature ( r t ) is a true radius of curvature that can better represent the corneal shape and local curvature changes. In 2012, Ying et al [ 6 ] proposed a method for calculating the corneal asphericity ( Q ) and analyze the characteristics of the anterior corneal shape using the tangential radius. In 2013, Zheng et al [ 7 ] elucidated the 360-semimeridional variation rule of the Q value using the polynomial fitting and constructed a customized 3-D model of the anterior corneal surface.…”
Section: Introductionmentioning
confidence: 99%